Evaluation of antioxidant activity of face mask combination formula rice (Oryza sativa L.) and jicama (Pachyrhizus erosus L.) - Kurniawati, Triani; Jehan, Nabila Nauli; Rahasasti, Indri Dwi; Jumaroh, Jumaroh (Borobudur Pharmacy Review, 2025)
Masks are traditional cosmetic products that contain minerals, vitamins, and proteins, useful for cleaning, brightening, tightening, moisturizing, and preventing premature aging of the skin. This study aims to evaluate the preparation of a combination of rice and yam bean mask through preparation evaluation tests, specific and non-specific standardization, and antioxidant activity tests. The method used was experimental with purposive sampling and antioxidant activity testing using UV-Vis spectrophotometry. Phytochemical results showed that rice contains alkaloids, while yam bean contains alkaloids, tannins, and phenols. All formulations passed the preparation evaluation test and non-specific standards according to the Indonesian Pharmacopoeia Edition VI. The IC₅₀ values ​​of antioxidant activity for the five formulations were 41.15; 25.06; 29.11; 24.27; and 35.58 µg/mL, respectively. The results of One-Way ANOVA showed no significant difference between formulations (p ≥ 0.05).